2005
DOI: 10.1345/aph.1e186
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pentoxifylline and Vitamin E in Attenuation of Radiation-Induced Fibrosis

Abstract: Overall, pentoxifylline is well tolerated and is one of the few commercially available drugs with clinical data for management of RIF. Despite a lack of large, well-designed clinical trials, pentoxifylline plus vitamin E should be considered as an option in patients with symptomatic RIF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 26 publications
(65 reference statements)
0
33
0
Order By: Relevance
“…[103][104][105][106] These medications have been recommended by some authors, despite the lack of large randomised-controlled trials (RCTs). 107 …”
Section: Abdominal Visceral Painmentioning
confidence: 99%
“…[103][104][105][106] These medications have been recommended by some authors, despite the lack of large randomised-controlled trials (RCTs). 107 …”
Section: Abdominal Visceral Painmentioning
confidence: 99%
“…Its derivatives exhibit protective effects against DNA damage (Sweetman et al 1997, Kumar et al 2002. The combination of PTX and aT was shown to reduce late chronic damage, fibrosis and necrosis in vivo , Letur-Konirsch et al 2002, Delanian & Lefaix 2002, Chiao & Lee 2005, whereas aT or PTX alone had no beneficial or toxic effects (Delanian et al 2003, Chiao & Lee 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Though the previous studies suggested that PTX or Vit. E alone was unable to reverse human RIF, they possessed all the major properties necessary to make them antifibrotic agents (25). Haddad reported 34 radiation-induced superficial fibrotic lesions were treated with PTX and Vit.…”
Section: Design Of the Studymentioning
confidence: 99%